Discovery of novel 2-(4-(benzyloxy)-5-(hydroxyl) phenyl) benzothiazole derivatives as multifunctional MAO-B inhibitors for the treatment of Parkinson's disease - Zhongcheng Cao; Xingyue Wang; Tianlong Zhang; Xianwu Fu; Fan Zhang; Jiang Zhu (Taylor & Francis Group, 2023)
To discover novel multifunctional agents for the treatment of Parkinson's disease, a series of 2-(4-(benzyloxy)-5-(hydroxyl) phenyl) benzothiazole derivatives was designed, synthesized and evaluated. The results revealed that representative compound 3h possessed potent and selective MAO-B inhibitory activity (IC50 = 0.062 µM), and its inhibitory mode was competitive and reversible. Additionally, 3h also displayed excellent anti-oxidative effect (ORAC = 2.27 Trolox equivalent), significant metal chelating ability and appropriate BBB permeability. Moreover, 3h exhibited good neuroprotective effect and anti-neuroinflammtory ability. These results indicated that compound 3h was a promising candidate for further development against PD.